A STUDY ON ATTITUDE OF CUSTOMERS TOWARDS ARTIFICIAL INTELLIGENCE IN BANKING IN TIRUNELVELI DISTRICT - Krishnammal, S. Muthu; U. Jothimani; Perumal, K. Arunachala (ShodhKosh: Journal of Visual and Performing Arts, 2024)
With Artificial Intelligence technologies increasingly integrated into various banking functions such as customer service, fraud detection, and personalized financial planning, understanding customer perceptions becomes critical for effective implementation. Through a survey of 50 respondents, this research explores customer awareness, trust, and concerns regarding AI in banking. The findings indicate a generally positive attitude towards AI, with respondents appreciating its potential for improving banking efficiency and convenience. However, concerns about data privacy and the ethical implications of AI remain significant. The study concludes that while customers are receptive to AI, banks must address concerns through transparent practices and robust data security measures to build trust and ensure broader acceptance.